Dynamic power control scheme based on fractional frequency reuse for D2D communication - Xianchao WANG; Fan JIANG; Changyin SUN; Chenbi LI; Binyan SHEN (Dianxin kexue)
By reusing the resource of existing cellular users,D2D (device-to-device)communication underlaying cellular network can improve the spectrum utilization rate and reduce the power consumption of mobile terminals.However,it will bring interference to the existing cellular networks.In order to ensure the quality of service of D2D users and cellular users,the power control and resource allocation scheme for D2D communication underlaying cellular communications was studied.Specifically,fractional frequency reuse was introduced to achieve the resource partitioning and resource reuse between cellular users and D2D users.Based on the principle of maximizing the throughput of the whole system,the optimization objective was established.Combined with the fractional power control and introduction of interference limits,a dynamic power control strategy was proposed.Simulation results show that the proposed scheme improves the performance of the overall system.